The lead-up to Mount Etna’s most destructive historic eruption (1669): cryptic recharge recorded in clinopyroxene - Magee, Ruadhán; Ubide Garralda, Teresa; Kahl, Maren (Journal of petrology, 2020)
An understanding of destructive historic eruptions has important implications for the assessment of active plumbing systems and the processes that might precede future hazardous eruptions. At Mount Etna (Sicily, Italy), magma production and eruption frequency have increased dramatically since 1970, however, the recent eruptions are considerably less voluminous than those of the 17th century, which occurred at greater intervals. Seventeenth century activity culminated in the 1669 flank eruption, the most voluminous and destructive in Etna’s recorded history, marking the beginning of a new eruptive period. In this study, we examine trace element zoning patterns recorded in clinopyroxene (lava hosted microcrysts: 0·5-1 mm, lava hosted macrocrysts: 1-5 mm and scoria hosted megacrysts: >5 mm) to reconstruct magma dynamics leading up to the 1669 eruption. The clinopyroxene data are considered alongside previous studies of olivine and plagioclase to present an updated conceptual model for the plumbing system, providing a better understanding of magmatic processes in the lead up to hazardous volcanism. Petrological observations in combination with laser ablation ICP-MS mapping reveal sharp compositional zoning of clinopyroxene, not seen in major element transects. Trace element data, including Cr, Zr, Ni and rare earth elements, show that core, mantle and rim regions originated in distinct magmatic environments. Chromium-rich cores (up to 1080 ppm Cr) are in disequilibrium with the glassy-microcrystalline host groundmass and indicate crystal inheritance from a primitive magma source. Oscillatory zoning in the mantle of the crystals suggests a sustained period of magma replenishment and crystallization. Finally, ubiquitous Cr-rich (170-220 ppm) rims host many large melt inclusions, suggesting a final recharge event inducing relatively rapid crystal growth and eruption. Temperatures of 1120-1160 ± 27°C and pressures of 300-600 ± 200 MPa calculated for the three magmatic environments based on clinopyroxene composition at 2 wt % H2O place most of the clinopyroxene crystallization at more than 10 km depth. Measuring the consistent thickness of crystal rims (219 ± 33 µm) and assuming growth at a low degree of undercooling (10−8 cm/s), we calculate that the eruption triggering magma recharge invaded the plumbing system less than a month before eruption onset, in agreement with historical accounts of pre-eruptive seismicity. Notably, Cr enrichment in the recharge magma was not coupled with increases in MgO content. We therefore propose that a cryptic recharge with similar composition to the resident melt may have tipped the system to erupt, and that the volume of recharge rather than composition or temperature acted as the primary trigger. Finally, LA-ICP-MS maps of clinopyroxene from the previous eruption of Mount Etna (1651-53) revealed strikingly similar compositional zonation to that of 1669, supporting the notion that magmatic storage environments, associated with voluminous 17th century activity, were long-lived.